2021
DOI: 10.1002/mc.23375
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: LINC02381 aggravates breast cancer through the miR‐1271‐5p/FN1 axis to activate PI3K/AKT pathway

Abstract: Emerging investigations have demonstrated that lncRNAs are key crucial modulators in cancer. In this study, we investigated the role of LINC02381 in breast cancer (BC). Reverse transcriptase quantitative polymerase chain reaction measured the LINC02381 level in BC tissues and cells. Colony formation, EdU staining, wound healing and Transwell experiments examined the impact of LINC02381 depletion on BC cell phenotypes. Relationship among miR‐1271‐5p, LINC02381, and FN1 was tested through applying RIP, luciferas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 39 publications
2
16
0
Order By: Relevance
“…FN1 encodes fibronectin, an ECM glycoprotein involved in cell adhesion and migration. FN1 plays a critical role in the development of ovarian ( Liang et al, 2020 ), thyroid ( Geng et al, 2021 ), renal ( Waalkes et al, 2010 ), cervical ( Zhou et al, 2019a ), breast ( Huang et al, 2022 ), and gastric cancers ( Han et al, 2020 ). Liu et al (2020) reported that the expression level of FN1 is also correlated with a poor HNSCC prognosis and that p62/SQSTM1 may participate as an autophagy adapter in the autophagy-lysosome pathway for FN1 degradation.…”
Section: Discussionmentioning
confidence: 99%
“…FN1 encodes fibronectin, an ECM glycoprotein involved in cell adhesion and migration. FN1 plays a critical role in the development of ovarian ( Liang et al, 2020 ), thyroid ( Geng et al, 2021 ), renal ( Waalkes et al, 2010 ), cervical ( Zhou et al, 2019a ), breast ( Huang et al, 2022 ), and gastric cancers ( Han et al, 2020 ). Liu et al (2020) reported that the expression level of FN1 is also correlated with a poor HNSCC prognosis and that p62/SQSTM1 may participate as an autophagy adapter in the autophagy-lysosome pathway for FN1 degradation.…”
Section: Discussionmentioning
confidence: 99%
“…In cancer-related research, miR-1271-5p is considered to be a tumor suppressor. MiR-1271-5p had been verified to decrease proliferation and metastasis in breast cancer [23] and glioma [24]. Also, studies had indicated that miR-1271-5p enhanced the cisplatin sensitivity of ovarian cancer by inhibiting cell growth and metastasis [25].…”
Section: Discussionmentioning
confidence: 99%
“…Survival analysis revealed that patients in the high-risk group had a much worse prognosis. Moreover, patients with high expression levels of seven GT-related lncRNAs turned cancer cells, including cell proliferation, migration, and invasion (45). Moreover, LINC02381 plays an oncogenic role in cervical cancer and osteosarcoma (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al. found that LINC02381 was upregulated in breast cancer, and knockdown of LINC02381 impaired the malignant phenotypes of breast cancer cells, including cell proliferation, migration, and invasion ( 45 ). Moreover, LINC02381 plays an oncogenic role in cervical cancer and osteosarcoma ( 46 , 47 ).…”
Section: Discussionmentioning
confidence: 99%